HGG-42. GLIOMA ONCOGENESIS IN CONSTITUTIONNAL MISMATCH REPAIR DEFICIENCY (CMMRD) SYNDROME: A CLINICO-PATHOLOGICAL AND MOLECULAR STUDY IN 15 PATIENTS. Issue 2 (22nd June 2018) - Merlevede, Jane; Andreiuolo, Felipe; Debily, Marie-Anne; Guerrini-Rousseau, Lea; Picot, Stephanie; Barret, Emilie; Lavoine, Noémie; Castel, David; Puget, Stephanie; Brugieres, Laurence; Varlet, Pascale; Grill, Jacques
Abstract: Glioma are frequently seen in the second decade of life in children with constitutional mismatch repair deficiency (CMMRD) syndrome. They are often associated with a high mutation load but their characteristics have not been extensively described. Your study describes 15 cases including 2 siblings from the radiological, histological et molecular (Whole Exome Sequencing) points of view. Tumors were frequently associated with lesions of different ages (multicentric) or vascular malformations. Different histologies were observed with a majority of glioblastomas (n=9) and giant tumor cells were almost always present. Immunohistochemistry was positive for p53 in 14/15 (concordant with mutations detected with sequencing) and was negative for ATRX in 11/15 (concordant with mutations detected with sequencing in all but one patient). PDL1 expression was only seen in 6/15. Mutation load was above 100/Mb in all but four; all hypermutated tumors had secondary mutations in POLE or POLD1. PMS2 and MSH2 were the two most frequently MMR genes mutated. The distribution of the variant allele frequency was most frequently bi- or tri-modal suggesting different waves of mutations gains. SomaticSignatures and DeconstructSig identified various combinations of signatures in the different exomes. Qualitatively mutations observed in the CMMRD samples were different from those observed in common pediatric high-grade gliomas (pHGG): absence of K27M and G34R/V mutations in H3F3A, absence of BRAF V600E mutation, absence of IDH1 R132H mutation, TP53 mutations were present in all but one. In conclusion, CMMRD-associated gliomas represent a distinct entity of pHGG with a specific oncogenesis.